John Searle and the construction of social reality - Rust, Joshua (Continuum studies in American philosophy., 2006)
Not only discloses the institutional backdrop against which speech takes place, also initiates a 'philosophy of society'. In locating The Construction of Social Reality, this book not only makes John Searle's text accessible to the readers in the social sciences, but presents Max Weber as a thinker worthy of philosophical reconsideration.